An Image Compression: - A Survey - Praba, V.Lakshmi; Rajesh, RS; Anitha, S (International Journal of Computer Sciences and Engineering, 2025)
Image compression is a challenging field in this era of communication. There is a need to learn and examine the literature of image compression, as the demand for images, video sequences and computer animation has increased at very high rate so that the increment is radically over the years. In this paper we illustrate some current developments that have taken place in still image compression. We deal with about special compression methods and also provide a performance comparison. Functionality and morality of compression methods are discussed in a unified manner. This survey reviews more recent articles on image compression and discuss their role in current research directions. There are several image compression algorithms some of them are lossy and some of them are lossless. Thus medical image, pre press industry, art work, remote sensing images for lossless image compression